Reconstruction of the Early Miocene Critical Zone at Loperot, Southwestern Turkana, Kenya - Liutkus-Pierce, Cynthia M.; Takashita-Bynum, Kevin K.; Beane, Luke A.; Edwards, Cole T.; Burns, Oliver E.; Mana, Sara; Hemming, Sidney; Grossman, Aryeh; Wright, James D.; Kirera, Francis M. (Frontiers in Ecology and Evolution, 2019)
The Hominoidea (apes and, eventually, humans) and Cercopithecoidea (Old World monkeys) diverged from a common ancestor during the late Oligocene ( 25 Ma) in East Africa. Subsequently, both catarrhine groups diversified in the early Miocene ( 23-16 Ma), making this time period an extremely important one for understanding our (deep) ancestral roots and the link between our hominoid ancestors and the environment. A remote region of west Turkana known as Loperot provides an exciting opportunity to study early Miocene primate paleoecology and has the potential to reveal the phylogenetic relationship between cercopithecoid monkeys and stem hominoids. The site of LpM4 is particularly fossiliferous and has produced a diverse fauna that includes several catarrhine fossils that await description. Radioisotopic dating indicates that the Loperot fauna are older than 17 Ma (early Miocene). Using geochemical data from paleosols and stable isotope values from rhizolith calcite, coupled with detailed sedimentology and stratigraphy, we reconstruct the early Miocene Critical Zone of Loperot to reveal a large perennial river system fed by ephemeral streams that created localized riparian forest microhabitats within a larger open ecosystem under semi-arid climate conditions, making Loperot's environmental reconstruction unlike many other early Miocene catarrhine-bearing localities. The perennial river system supported corridors of C3 forests; however, because these forests were restricted, they could not support a high diversity of forest indicator taxa. This is the most comprehensive analysis of the environmental conditions at Loperot to date, and provides new empirical evidence to suggest that African climate varied significantly by region and that arid habitats certainly existed during the early Miocene.